Optimized coverage enhancement and performance analysis of Wi-Fi 7 networks with 5G and small cell integration in high-density environments - Kadhim, Mohammed Aboud; Ibraheem, Zeyid T; Ali, Mohammed Hussain (International Journal of Innovative Research and Scientific Studies, 2025)
With the increasing demand for higher data rates, lower latency, and better network efficiency provided by high-density environments, wireless technologies are developing at an unprecedented pace, especially in the form of wireless fidelity Wi-Fi 7. Although Wi-Fi 7 significantly improves on prior generations, it encounters difficulties in dense urban environments where channel contention, interference, and congestion can lead to performance degradation. To address these challenges, this paper investigates the convergence of fifth-generation (5G) networks and small cells with Wi-Fi 7 for increased coverage, low latency, and high throughput. By using the new approach, low-latency and high-capacity features of 5G access are merged with localized network coverage from small cells to prevent performance bottlenecks of conventional Wi-Fi 7. It is evaluated via extensive simulations how this integration affects the key performance metrics: latency, throughput, and collision rates. There have been significant improvements in network performance, particularly in high-device-density environments when compared to standard Wi-Fi 7 configurations, as demonstrated by the results. This study provides valuable insight into understanding the advantages of 5G and integration aspects, thereby aiding in the design of future-generation cellular networks in urban/high-density scenarios where Wi-Fi 7 capabilities are enhanced.